Strategi Manajemen dalam Meningkatkan Kinerja Karyawan pada PT. Agta Sinar Jaya di Bandar Lampung - Suryani Suryani (Business Perspective Journal, 2023)
The purpose of this study was to determine the implementation of management strategies in improving employee performance at PT. Agta Sinar Jaya in Bandar Lampung, to explain the relationship of work discipline to the performance of employees of PT. Agta Sinar Jaya in Bandar Lampung, and to explain the evaluation of management strategies in improving the performance of employees of PT. Agta Sinar Jaya in Bandar Lampung. The type of research used is field research, which is descriptive in nature with a qualitative approach to obtain data that is relevant to the research being conducted. The required data was obtained through interviews conducted with a company director and several employees who were the source of research data at PT. Agta Sinar Jaya. The research results shown that management strategies in improving employee performance at PT. Agta Sinar Jaya still has not been implemented properly, because of the rolling position system, so that employees don't understand their respective new positions and need time to adapt first so they can do their jobs well. Management strategy on discipline in improving performance at PT. Agta Sinar Jaya, there are still about 80% of employees who are not disciplined. Evaluation of management strategies in improving performance at PT. Agta Sinar Jaya, in general, employees work well after attending debriefing and training and applying discipline by giving rewards and punishments. Keywords: performance, management, strategy